High school athletic directors’ perceptions of athletic coaching: a survey study of the applicability of Charlotte Danielson’s Framework for Teaching to coaching - Oliver, Erin Lynn (Kansas State University, 2020)
The purpose of this study was to identify the underlying dimensions that influence high school athletic director’s view of effective high school athletic coaching. By identifying these factors, it was determined if high school athletic directors agree that the components for effective athletic coaching run parallel to Charlotte Danielson’s (2013) framework for effective teaching since athletic coaching is a form of teaching. The study surveyed high school athletic directors in Kansas using a modified version of the Framework for Teaching Survey developed by Sweeley (2004). The study also identified if various factors such as school size, years of experience as athletic director, and gender of the athletic director influenced athletic director’s opinions of effective high school athletic coaching. An exploratory factor analysis was conducted using direct oblimin as the oblique rotation method and principal axis factoring as the extraction method. The factor analysis revealed three factors representing the underlying dimensions of athletic director views, namely, Coaching Culture, Content Knowledge, and Servant Leadership. Using the raw mean factor score for each participant calculated, the multivariate analysis of variance (MANOVA) did not find any significant relationships existed between the identified factors and the independent variables of school size, years of experience, and gender. Overall, the results supported that Charlotte Danielson’s (2013) Framework for Teaching was applicable when applied to effective high school athletic coaching and could be applied to all high school sports of all levels for both head and assistant coaches.
Keywords: High school athletic coaching evaluations; High school athletic director's perceptions of athletic coaching; High school athletic coaching; Charlotte Danielson's Framework for Teaching